'Models of possible selves: teachers' reflections on childhood memories of parents'. Issue 4 (2nd October 2022) - Chang-Kredl, Sandra; Garlen, Julie; Sonu, Debbie; Farley, Lisa
ABSTRACT: This study draws from theories of attachment to examine prospective teachers' reflections on the role of the parent in their childhood memories in shaping the imagination of their future selves. As part of a larger qualitative study, we collected and analyzed the memory narratives of teacher candidates and undergraduate students preparing to work with children, and selected 53 of the 116 narratives that featured parents. These memories demonstrate three ways in which parents figured into the participants'memories and reflections on their motivations to work with children: 1) as supportive role models, 2) as catalysts of sympathy for children whom teachers imagine as lacking the privileges their own parents provided, and 3) as spurs for empathy towards children whom they identify with as experiencing challenging situations. In each case, the participant created an internal working model of the child-adult relationship in their memory and imagined themselves taking up a parallel role as the adult in a future child-adult relationship. As teacher educators concerned with the identity work of preservice teachers, our findings highlight the importance of critically exploring childhood memories of parents as models for the teacher-child relationship.